Monitoring carotid blood flow and ECG for cardiovascular disease in elder subjects - Noor Azmi, Azran Azhim; Yamaguchi, Hisao; Hirao, Yuji; Kinouchi, Yohsuke; Yamaguchi, Hisao; Yoshizaki, Kazuo; Ito, S; Nomura, Masaharu (IEEE, 2005)
This report is to investigate the correlation between common carotid blood flow (CCBF) properties and the risk factors for cardiovascular disease. The measurement system was designed for simultaneously monitoring of CCBF and electrocardiogram (ECG) in order to get more valid information for detection and diagnosis of cardiovascular disease. In our study, blood flow velocimeter was developed to measure blood flow in carotid by using ultrasound Doppler technique. This measurement system is based on a continuous-wave (CW) Doppler ultrasound method with two semicircular piezoelectric (PZT) transducers, one continuously transmitting ultrasound, and the other continuously receiving the echoes. Eleven patients with cardiovascular disease underwent in the experiment. In the report, blood flow was compared with data from 25 healthy subjects which asymptomatic subjects putatively free of cardiovascular disease as controls. The maximum of CCBF velocity was 102.8 (SD 18.3) cm/s in the 25 healthy subjects. While, the maximum of CCBF velocities were 53.9 (SD 16.6) cm/s in the eleven cardiac patients. The data suggest that CCBF velocity decreased significantly in the cardiac patients and by simultaneously monitoring of CCBF and ECG were probably obtained more valid information to detect and diagnose cardiovascular disease at the early stage.